La place du tissu phraséologique dans l’élaboration des discours et sa didactisation (PHRASIS | Rivista di studi fraseologici e paremiologici, 2021)
The presence of a phraseosystem in discourse, as highlighted by corpus linguistics and linguistic statistics, makes it possible to ensure the existence of a phraseological fabric at work in the elaboration of texts. This fabric is composed of elements linked on the syntagmatic axis and distributed along the length of the text to guarantee its cohesion and coherence. However, the way they operate in the construction of texts gives the phraseological units a structuring function that should be mastered when learning a language, maternal or foreign. To do this, in this study we propose a typology of these elements, divided into arguments, connectors and modalizers, as well as a pedagogical model to be applied so that phraseological competence becomes an objective of explicit teaching in the educational curriculum of the pupils, whether they are learning in their mother tongue or in a foreign language.
Keywords: phraseology, phraseological fabric, typology, pedagogical model, phraseological competence